Reciprocal Relationship between Lecturer Performance and Implementation UKI’s Values at Universitas Kristen Indonesia - Dirk Roy Kolibu; Wellem Sairwona (GoAcademica Research & Publishing, 2021)
The implementation of the values of Universitas Kristen Indonesia (UKI) is important to be applied and implemented in the education process to develop the quality of the lecturer's character so that its implementation can be seen through the behaviour that is reflected in a person which is a combination of all good values, including behaviour that must look like: humility, sharing and caring, discipline, professional, responsibility, and integrity. The benchmark is the courage to change its performance to become a positive and constructive work culture. This study uses a quantitative research design with a casual and interactive approach. This study found that: there is a positive and significant relationship between lecturer performance and the implementation of UKI values. The correlation coefficient is 0.612, determination is 37.4%, t-count (5,068) > (2,000), and the regression equation = 19.975 + 0.528X₁. The reciprocal relationship between lecturer performance and the implementation of UKI values is significant or positive. The higher the level of implementation of the UKI values, the higher the lecturer's performance. On the other hand, the higher the performance of the lecturers, the more they support the implementation of the UKI values. The conclusion is that implementing UKI values in academic activities or academic support will develop character qualities or personal qualities, which tend to determine the quality of one's relationships with other people and their relationship with the environment in which they are located.